GAMBARAN KARAKTERISTIK DAN FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIABETES MELITUS TIPE 2 PADA WANITA (Studi di RSUD Kardinah Kota Tegal) - Fadilah, Nurul Aini; Saraswati, Lintang Dian; Adi, Mateus Sakundarno (Jurnal Kesehatan Masyarakat (Undip), 2016)
Diabetes Mellitus (DM) Type 2 is a metabolic disorder characterized by the increase in blood sugar due to a decrease in insulin secretion by pancreatic beta cells and or decreased insulin function (insulin resistance). In Tegal, the largest case proportion of Type 2 diabetes (37.4%) were from Kardinah Hospital patients. Amounted to 60.58% in 2012, 61.56% in 2013, and 63.39% in 2014 of all cases of Type 2 diabetes in Kardinah Hospital were women. The purposes of this study were to describe the characteristics and factors related to the incidence of Type 2 diabetes in women. Type of this study was observational descriptive with cross sectional design. The subjects of research were new women patients with Type 2 diabetes amounted to 100 people. The sampling technique used was consecutive sampling. The study concluded that 49% of respondents had family history of diabetes, 68% of respondents were obese, 54% of respondents with hypertension, 45% of respondents were less physical activity, 16% of respondents had age of menarche at ≤11 years old, 78% of respondents had parity ≥3, 48% of respondents had high levels of stress, 16.3% of respondents had a history of gestational diabetes mellitus, and 56% of respondents had sleep disorder. It also known that 70% of respondents had >3 factors related to the incidence of Type 2 diabetes in women, 40% of respondents had parity ≥5, and 73.5% of respondents had one family member with history of DM. Advices that were given to patients are to lose weight, maintain blood pressure, and sleep regularly. Suggestion for hospital organizer is to conduct a routine inspection of body weight at each visit, and for other researchers is to conduct further research on parity, obesity, sleep disorders with Type 2 diabetes in women.